PO086 European registry of corticobasal degeneration a prospect sister study: recruitment of patients with corticobasal syndrome via the bnsu. (1st December 2017) - Lamb, Ruth; Darvell, Marcia; Woodside, John; Weil, Rimona; Rohrer, Jonathan; Lees, Andrew; Morris, Huw
Abstract : Corticobasal degeneration (CBD) is a rare progressive neurodegenerative disease. Our primary aim is to investigate how clinical and biological features can help explain the varying pathology that underlies corticobasal syndrome (CBS) and to define the markers of pathological CBD. The secondary aim is to establish a cohort of patients with clinically well-defined CBS that will be available for future therapeutic and clinical studies. The ABN BNSU is a source of recruitment of patients with CBS to the PROSPECT study. Eligible patients are notified to the study team monthly by ABN members. Patients are provided with a permission to contact form. Following informed consent, patients provide blood samples for genetic analysis and cell lines and complete study questionnaires. Patients can participate remotely or at their local study site. We have received 22 BNSU referrals from 22 consultants over 5 months (mean 4.5/month). So far we have received 1 permission to contact form from a patient who is being recruited to study. The BNSU is an invaluable source of referrals for patients with rare diseases from across the UK. There is a 4 month delay from initial contact to return of reply forms and we will investigate ways to streamline the recruitment process.